Gut Microbiome Composition in Non-human Primates Consuming a Western or Mediterranean Diet - Nagpal, Ravinder; Shively, Carol A.; Appt, Susan A.; Register, Thomas C.; Michalson, Kristofer T.; Vitolins, Mara Z.; Yadav, Hariom (Frontiers in Nutrition, 2018)
The mammalian gastrointestinal tract harbors a highly diverse and dynamic community of bacteria. The array of this gut bacterial community, which functions collectively as a fully unified organ in the host metabolism, varies greatly among different host species and can be shaped by long-term nutritional interventions. Non-human primates, our close phylogenetic relatives and ancestors, provide an excellent model for studying diet-microbiome interaction; however, compared to clinical and rodent studies, research targeting primate gut microbiome has been limited. Herein, we analyze the gut microbiome composition in female cynomolgus macaques (Macaca fascicularis; n=20) after the long-term (2.5 years) consumption of diets designed to mimic recent human Western- (WD; n=10) or Mediterranean-type (MD; n=10) diets. Microbiome diversity in MD consumers was significantly higher by the Shannon diversity index compared to the WD consumers, with similar but non-significant trends noted for the diversity metrics of species richness (Chao 1), observed operational taxonomic units (OTUs) and phylogenetic diversity (PD) whole Tree. Compared to the MD, the WD group demonstrated a higher Firmicutes-Bacteroides ratio and a significantly higher abundance of families Clostridiacea and Lactobacillaceae. Further analyses reveal significantly higher abundance of genera Lactobacillus, Clostridium, Faecalibacterium and Oscillospira and lower abundance of Ruminococcus and Coprococcus in MD consumers relative to WD consumers. OTUs belonging to several species also show significant differences between the two groups, with Lactobacillus species demonstrating a prominently higher abundance in the MD consumers. The data reveal several differences in the gut microbiome of primates consuming the two different diets and should be useful for further studies aimed at understanding the diet-microbiome-health interactions in primates.